Pengaruh Tingkat Motivasi terhadap Pengambilan Keputusan dalam Membuka Bidang Usaha Produktif bagi Mahasiswa Fakultas Ekonomi di Institut Syekh Abdul Halim Hasan Binjai - Khairina Khairina; Zunaida Riska; Yudistira Abdi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to determine the influence of motivation levels on the decision-making process regarding the establishment of productive business ventures among students of the Faculty of Economics. The study employs quantitative research with an associative approach. Primary data were collected by distributing a questionnaire via Google Forms to 50 respondents, comprising 30 questions or statements. Purposive sampling was used as the sampling technique. Data processing was conducted using SPSS version 25 for Windows. The results indicate that motivation has a positive and significant influence on students' decisions to start a business, as evidenced by a significance value of 0.003 (which is less than 0.05) and a calculated t-value of 5.394 (which exceeds the t-table value of 1.686). Furthermore, the study found a substantial influence of 34.6%, while the remaining 69.4% is attributed to variables outside the scope of this research.